Negotiating Religious Identity In Religious Moderation: A Case Of Islamic University - Miftah, Muhammad; Erzad, Azizah Maulina (Nadwa: Jurnal Pendidikan Islam, 2024)
Religious Moderation has been an important program in Islamic Higher Education since 2019. This program contributes to the spread of moderate religious views among Islamic higher education stakeholders. This research is qualitative research conducted at UIN Raden Mas Said Surakarta. The results of this study indicate that there were variations of religious identities in responding to religious moderation as can be seen from various extra-campus affiliated with mass organizations. Some extra-campus organizations were not inclined toward religious moderation values. These religious identities can be seen from the extra-campus at UIN Surakarta, including IMAMTA, HMI, PMII, IMM, and KAMMI which have various perspectives, perceptions, receptions, acceptance patterns, interactions, and relations of each mass organization concerning religious moderation. This study indicated that religious identities that have metamorphosed into extra-campus organizations have an opportunity to be explored to propose a more nuanced religious moderation at the university level.